Intensitas Paparan Sinar Uv Terhadap Tajam Penglihatan Pada Pengemudi Ojek Online Di Ciputat Timur 2022 - Husein, Mohammad (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2023)
Geographically, Indonesia is a country located in the equator which has a tropical climate with sun exposure throughout the season. In addition, many of the livelihoods of the Indonesian people are workers who do a lot of outdoor activities so that they get direct sun exposure and if they receive sun exposure with excessive intensity, this is very vulnerable to eye health. The purpose of this study was to determine how the intensity of UV light exposure on the quality of visual acuity is described. This research is a quantitative descriptive study, which aims to see how the intensity of UV light exposure on the quality of visual acuity of online motorcycle taxi drivers in Ciputat Timur uses a Cross Sectional approach where the research subjects are only examined once at a time. From the results of the quality inspection of visual acuity, the majority of online motorcycle taxi drivers have good vision, namely 20/20 for the right eye as many as 22 people or 55% of the total number of respondents and the left eye as many as 28 people or 70% of the total number of respondents.